2017
DOI: 10.3390/ijms18122531
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Maintaining Renal Epithelial Barrier Function in Uremic Conditions

Abstract: As current kidney replacement therapies are not efficient enough for end-stage renal disease (ESRD) treatment, a bioartificial kidney (BAK) device, based on conditionally immortalized human proximal tubule epithelial cells (ciPTEC), could represent an attractive solution. The active transport activity of such a system was recently demonstrated. In addition, endocrine functions of the cells, such as vitamin D activation, are relevant. The organic anion transporter 1 (OAT-1) overexpressing ciPTEC line presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Flow through the basolateral compartment is also possible. Exposure of these hollow fibres to uraemic toxins increased IL-6 expression and induced leakage of FITC-labelled inulin, indicating disruption of the epithelial tight junctions 145 . Notably, the convex arrangement of tubular epithelial cells on the exterior of the hollow fibre is not reflective of their arrangement in vivo — a caveat that should be addressed in future designs.…”
Section: Preclinical Screens Of Nephrotoxicitymentioning
confidence: 99%
“…Flow through the basolateral compartment is also possible. Exposure of these hollow fibres to uraemic toxins increased IL-6 expression and induced leakage of FITC-labelled inulin, indicating disruption of the epithelial tight junctions 145 . Notably, the convex arrangement of tubular epithelial cells on the exterior of the hollow fibre is not reflective of their arrangement in vivo — a caveat that should be addressed in future designs.…”
Section: Preclinical Screens Of Nephrotoxicitymentioning
confidence: 99%
“…Calcitriol regulates antimicrobial proteins (cathelicidin and β-defensin), responsible for modifying intestinal microbiota to a healthier composition and supporting the gut barrier [10,14], as well as protecting the lungs against infection [15]; increases tight junction protein expression, E-cadherin, and connexion 43 in the gut [16][17][18]; maintains renal epithelial barrier function [19]; enhances corneal epithelial barrier function [20] Vitamin C…”
Section: Physical and Biochemical Barriersmentioning
confidence: 99%
“…It also stimulates tight junction protein expression, E-cadherin, and connexin 43 in the gastrointestinal tract, which function as structural precursors of gap junctions and provide a communication pathway between the cytosol and extracellular environment of the intestinal barrier [16][17][18]. They also maintain renal epithelial barrier function [19], and enhance corneal epithelial barrier function [20]. The gastrointestinal tract is an important line of defense in which epithelial cells provide a physical and biochemical barrier and work in concert with immune cells and the gut microflora (some of which produce an array of compounds such as bacteriocins) to strengthen the gut barrier, fight off pathogens, and limit their direct contact with the epithelium [81].…”
Section: Physical and Biochemical Barriersmentioning
confidence: 99%
“…[62a,76a] The ciPTEC were also shown to secrete an active form of vitamin D when exposed to a mix of uremic toxins at concentrations that match those found in CKD patients. [79] Considering the progressive reduction of active vitamin D in these patients, this feature could be an exquisite addition to the function of the BAK system. Moreover, it has been reported that conventional hemodialysis removes vitamin D, [80] thus ciPTEC could become an important source of this metabolite.…”
Section: Stem Cells: Embryonic or Induced-pluripotent Tissue-derivedmentioning
confidence: 99%